Integration of Substance Abuse Treatment Organizations into Accountable Care Organizations: Results from a National Survey. - D'Aunno, Thomas; Friedmann, Peter D.; Qixuan Chen; Wilson, Donna M. (Journal of Health Politics, Policy & Law, 2015)
To meet their aims of managing population health to improve the quality and cost of health care in the United States, accountable care organizations (ACOs) will need to focus on coordinating care for individuals with substance abuse disorders. The prevalence of these disorders is high, and these individuals often suffer from comorbid chronic medical and social conditions. This article examines the extent to which the nation's fourteen thousand specialty substance abuse treatment (SAT) organizations, which have a daily census of more than 1 million patients, are contracting with ACOs across the country; we also examine factors associated with SAT organization involvement with ACOs. We draw on data from a recent (2014) nationally representative survey of executive directors and clinical supervisors from 635 SAT organizations. Results show that only 15 percent of these organizations had signed contracts with ACOs. Results from multivariate analyses show that directors' perceptions of market competition, organizational ownership, and geographic location are significantly related to SAT involvement with ACOs. We discuss implications for integrating the SAT specialty system with the mainstream health care system.